(untitled) - Michaud, Claude (New York, 2003)
This book argues that for many companies organization is designed to achieve operational optimization and may be in conflict with strategic objectives. Managers may not share similar decision criteria and this may facilitate or hinder the fulfillment of certain strategies. The role of top managers is to shape to a large extent the ability of the organizational system to implement and achieve strategic objectives. This book provides breakthrough thinking on these issues by two leading academic thinkers.
Keywords: Strategic planning,Communication in organizations,Organizational effectiveness,Management